A Qualitative Exploration of Cyber-Bystanders and Moral Engagement. (11th September 2013) - Price, Deborah; Green, Deborah; Spears, Barbara; Scrimgeour, Margaret; Barnes, Alan; Geer, Ruth; Johnson, Bruce
<x content-type="archive" xml:space="preserve">Abstract</x> Studies have found that moral disengagement plays a significant role in the continuation of bullying situations (Bonanno, 2005); however, the moral stance of cyber-bystanders — those who witness online bullying — is not yet clear. While research into traditional face-to-face bullying reported that peers would probably or certainly intervene to support victims in 43% of cases (Rigby & Johnson, 2006) actual intervention is reportedly much less (Atlas & Pepler, 1998; Craig & Pepler, 1997). Little is known, however, about the attitudes and behaviours of bystanders or witnesses when online, or their probable intentions to intervene. This study employed three digital animations of typical cyberbullying scenarios to explore young people's views of cyber-bystanders. Youth from Years 8–12 (mean age 15.06, N = 961) from one metropolitan secondary school in Adelaide, South Australia, completed an online survey after watching vignettes. To shed light on the rationale and thinking behind their understanding of bystanders and moral dis/engagement when online, this article reports on the qualitative responses from young people in relation to one of these animations/vignettes. The findings suggest that young people perceive cyber-bystanders to have the capacity to morally engage in cyberbullying incidents; however, there are various barriers to their active positive engagement. The implications can inform educators and school counsellors about possible ways to support students to intervene when they witness cyberbullying.